HE PROBLEM FACED IN WRITING THESIS BY EIGHTH SEMESTER STUDENTS OF ENGLISH EDUCATION PROGRAM FKIP-UMM IN ACADEMIC THE STUDENTS’ PROBLEMS IN WRITING AN UNDERGRADUATE THESIS: A CASE STUDY AT ENGLISH LANGUAGE TEACHING PROGRAM OF MUHAMMADIYAH UNIVERSITY OF MATARAM - Irwandi Irwandi (Muhammadiyah University of Mataram, 2017)
The purpose of this study was to investigate the problems faced by Eighth-semester students of English Education Program FKIP-UMM in the academic year 2015–2016 in writing thesis, especially in internal and external factors. This study used a case study. The subjects of this study were the Eighth-semester students who composed their thesis. In this study, the writer used purposive sampling as the sampling technique. So, the sample was 15 students. The instruments applied in this study were questionnaire and interview. The questionnaire was used for finding the students’ problems in writing a thesis. However, the interview was used to support the data obtained from the questionnaire. The result of this study showed that the problem faced in writing a thesis by Eighth-semester students of English Education Program, especially in internal and external factors. The first internal factors consisted of 33 % of students have a problem in deciding the title of thesis, 20 % of students did not understand how to write the organization of their thesis, 20 % of students have a problem in finding appropriate theories to support their thesis, 13 % of students have a problem in deciding methodology which is suitable. The external factor was 33 % of students said “No” library of the college provides a variety of books that can help them to write their thesis. Those problems are dominantly caused by internal factors rather than the external ones. The internal factors include the knowledge of students while the external factor related to the facility of college that support students in writing a thesis.